OPTIMAL DESIGN OF VARIABLE PITCH STRUCTURE IN VASCULAR STENTS TO PREVENT LOOP-END FRACTURE - XUE Guangming; MUHETAER Kelimu; LI Hong (Jixie qiangdu)
Aiming at the problem that loop-end braided stents are prone to loop-end fracture during crimping, the key design parameters affecting the structural stability of loop-end braided stents were explored, and an improvement scheme was proposed.Numerical simulation of crimping for magnesium alloy loop-end braided stents was conducted using Abaqus analysis software. The results showed that increasing the braiding angle can effectively reduce the risk of loop-end fracture. Based on this finding, a variable pitch stent was designed, which features increasing the braiding angle at both ends to form sparse segments while maintaining the braiding angle in the middle of the stent. The influence of adjusting the length and braiding angle of the sparse segments on the mechanical response of the stent was evaluated.The research results showed that increasing the braiding angle and length of the sparse segments can effectively reduce the axial elongation and loop-end stress of the stent, but it will shorten the length of the middle dense segment, thereby reducing the radial force of the stent. Different from the flared expansion of the constant pitch open-end stent, the variable pitch stent presents a shape with large middle expansion and small end expansion after expansion.This study reveals the potential of variable pitch design in controlling loop-end fracture and provides a reference for the structural optimization of magnesium alloy braided stents.